2022
DOI: 10.1007/s40647-021-00338-2
|View full text |Cite
|
Sign up to set email alerts
|

Global Justice and the Motivation to Give

Abstract: Cosmopolitans, statists and liberal nationalists disagree over the relevance of regulating substantive inequalities at the global level. This paper aims to resolve the dispute among these three schools of thought. I show firstly that cosmopolitans, statists, and liberal nationalists all aim to motivate people to give in support of distributive justice at the global level. However, cosmopolitans lack a substantive theory of how to develop sufficient motivation to give globally. Secondly, the statists’ account o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Basically, I agree with Liu ( 2022 : 215) that political participation without “a common national identity developed through the nation-building process” is insufficient to motivate people to support distributive justice and equality of conditions. However, political participation can also be part of the nation-building process to establish a common national identity.…”
Section: Beyond Equal Opportunity: Republican Democracymentioning
confidence: 88%
See 1 more Smart Citation
“…Basically, I agree with Liu ( 2022 : 215) that political participation without “a common national identity developed through the nation-building process” is insufficient to motivate people to support distributive justice and equality of conditions. However, political participation can also be part of the nation-building process to establish a common national identity.…”
Section: Beyond Equal Opportunity: Republican Democracymentioning
confidence: 88%
“…In addition, the problem of post-truth politics has made such political deliberation even more difficult. Siyang Liu ( 2022 : 16–8) refers to David Miller’s liberal nationalism and criticizes that political deliberation is insufficient to cultivate the sense of solidarity and motivate people to give in support of distributive justice, because it fails to explain why people are willing to engage in public deliberation without nationalist sentiments in the first place. While Baum ( 2012 : 726) strongly supports Tawney’s, as well as Sandel’s, democratic equality, he also admits that such an account “has a somewhat utopian character, pointing beyond the horizon of what currently is ‘realistic’ politically… In our era of transnational corporate power and diverse noneconomic (or not strictly economic) sources of political struggle, economic democratization may be harder than ever to realize.”…”
Section: Beyond Equal Opportunity: Republican Democracymentioning
confidence: 99%
“…Aid can help boost economies in low-and middle-income countries, but institutional strengthening is also needed to prevent corruption (Wang 2022). Furthermore, donor countries' efforts to aid developing nations can also positively impact their image (An and Feng 2022;Liu 2022). Li (2021) concluded that Chinese aid to African countries will be more effective when the US does not provide concurrent aid.…”
Section: Foreign Aid and Corruptionmentioning
confidence: 99%